Keikutsertaan Kanada dalam Perjanjian Trans-Pacific Partnership: Sebuah Analisis Liberal Intergovernmentalism - Rachmadea Aisyah (Department of International Relations, Brawijaya University, 2016)
In October 2012, Canada became one of the members of the Trans-Pacific Partnership (TPP) agreement negotiation, a blueprint of the largest free trade agreement in history that covers 12 Asia-Pacific countries and 40 percent of the world economy. This agreement was then signed by Canada and 11 other member countries in February 2016.Canada once rejected the invitation to join this agreement when it was still called TPSEP in 2005, but instead became observer and expressed its interest to join several years later. Canadaâ€™s wish to join was met by rejection from some of the TPP members, as well as from their own domestic social groups. After the signing, the rejection increased and Canadians considered that their government had failed to carry on their interests during the negotiation. Therefore, Canadaâ€™s approval on TPP despite disagreements from many groups was something peculiar.In this article, the author would look into this phenomenon through liberal intergovernmentalism, an international relations theory developed by Andrew Moravcsik focusing in regionalism. The first part of the article will discuss the methods of liberal integovernmentalism theory, whereas the second and third part will discuss the result of the analysis and the conclusion from this article.Â Keywords: TPP, Liberal Intergovernmentalism, Canada, preference